Chitosan/chondroitin sulfate membranes produced by polyelectrolyte complexation for cartilage engineering - Rodrigues, M. N. (2016)
Membranes made of chitosan (CHT) and chondroitin sulfate (CS) are herein presented using a polyelectrolyte complexation sedimentation/evaporation method. The membranes present high roughness and heterogeneous morphology induced by salt crystals. Exposing the membranes to different salt concentrations induces saloplastic behavior, as shown by an increasing water absorption and decreasing stiffness while exposed to increasing concentrations of salt. Establishing contact between two parts of a cut membrane leads to their self-adhesion and maintenance of their stretching ability. The membranes sustain the adhesion of ATDC5 prechondrocyte cells, inducing their rearrangement in cellular aggregates typical of chondrogenesis, and the expression of cartilage markers. Impregnated TGF-Î²3 remains loaded after 14 days of incubation, releasing only 1.2% of its total loaded mass. CHT/CS polyelectrolyte membranes are here shown as suitable candidates for the biomedical field, namely, for cartilage regeneration.